Methods and representativeness of a European survey in children and adolescents: the KIDSCREEN study - von Rueden Ursula; Duer Wolfgang; Bisegger Corinna; Tebé Cristian; Erhart Michael; Ravens-Sieberer Ulrike; Berra Silvina; Herdman Michael; Alonso Jordi; Rajmil Luis (BMC, 2007)
Abstract Background The objective of the present study was to compare three different sampling and questionnaire administration methods used in the international KIDSCREEN study in terms of participation, response rates, and external validity. Methods Children and adolescents aged 8-18 years were surveyed in 13 European countries using either telephone sampling and mail administration, random sampling of school listings followed by classroom or mail administration, or multistage random sampling of communities and households with self-administration of the survey materials at home. Cooperation, completion, and response rates were compared across countries and survey methods. Data on non-respondents was collected in 8 countries. The population fraction (PF, respondents in each sex-age, or educational level category, divided by the population in the same category from Eurostat census data) and population fraction ratio (PFR, ratio of PF) and their corresponding 95% confidence intervals were used to analyze differences by country between the KIDSCREEN samples and a reference Eurostat population. Results Response rates by country ranged from 18.9% to 91.2%. Response rates were highest in the school-based surveys (69.0%-91.2%). Sample proportions by age and gender were similar to the reference Eurostat population in most countries, although boys and adolescents were slightly underrepresented (PFR <1). Parents in lower educational categories were less likely to participate (PFR <1 in 5 countries). Parents in higher educational categories were overrepresented when the school and household sampling strategies were used (PFR = 1.78-2.97). Conclusion School-based sampling achieved the highest overall response rates but also produced slightly more biased samples than the other methods. The results suggest that the samples were sufficiently representative to provide reference population values for the KIDSCREEN instrument.